Perception of nudge interventions to mitigate medication errors risk in healthcare service delivery - Keng Sheng, Chew; Say Keat, Ooi; Noor Fareen, Abdul Rahim; Shirly Wong, Siew Ling; Vanitha, Kandasamy; Shin Shin, Teo (BioMed Central Ltd, 2023)
Background Conventional cognitive interventions to reduce medication errors have been found to be less effective as behavioural change does not always follow intention change. Nudge interventions, which subtly steer one’s choices, have recently been introduced. Methods Conducted from February to May 2023, this study aimed to determine the relationships between perceived effectiveness and perceived ease of implementation of six nudge interventions to reduce medication errors, i.e., provider champion, provider’s commitment, peer comparison, provider education, patient education and departmental feedback, and the moderating effects of seniority of job positions and clinical experience on nudge acceptability. Partial Least Square Structural Equation Modelling was used for data analysis. Results and discussion All six nudge strategies had significant positive relationships between perceived effectiveness and acceptability. In three out of six interventions, perceived ease of implementation was shown to have positive relationships with perceived acceptability. Only seniority of job position had a significant moderating effect on perceived ease of implementation in peer comparison intervention. Interventions that personally involve senior doctors appeared to have higher predictive accuracy than those that do not, indicating that high power-distance culture influence intervention acceptability. Conclusion For successful nudge implementations, both intrinsic properties of the interventions and the broader sociocultural context is necessary.